Analisis Kompetensi Pedagogik Guru MTS Laboratorium UINSU Medan Dalam Mengimplementasikan Kurikulum Merdeka di Era Digital - Fattah, Abdul; Daulay, Anysah; Lubis, Artika; Asri, Dwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Teacher pedagogical competence is a competency that teachers must have in the form of the ability to organize student learning in the classroom. The issue of this research is how teachers integrate pedagogical competence in the independent curriculum in the digital era at MTS LABORATORY UINSU. The type of research used focuses on in a qualitative approach that involves case studies. The data collection technique used is the observation method, interview and study documents. Interviews are often also said to be interviews conducted with Mrs. Helmiati S.Pd as an arts and culture teacher. Observations or observations are carried out to obtain accurate information from the research object. Documentation, in other words, document study is carried out in the first two sessions. during the interview and secondly when the interview process has been completed as research evidence. The research results show that the analysis of teacher pedagogical competence in implementing the independent curriculum in the digital era has not gone well in accordance with pedagogical competence due to the lack of supporting infrastructure for learning according to the independent curriculum in the digital era .